Determination of neutralization point for allergic hypersensitivity - Fox, Anthony D. (British Homeopathic Journal, 1987)
The electronic Vegatest method of determining environmental hypersensitivities (allergies) is fast, accurate, and does not require the use of any needle puncture of the skin of the patient. It provides a relatively reliable method of determining the neutralization point and is well suited to the use of homœopathic medicines.